A Study on the Effect of Residual Sodium Carbonate of Irrigation Water on the Properties of a Loamy Sand Soil and on Yield and Nutrient Uptake by Wheat and Barley - Lal, P; Mali, G C; Singh, K S (Annals of Arid Zone, 2016)
- Â